Dairy Farmer Resource Competency Development Model In Supporting The Development Of Tourism Village Area - Muhammad Aufa Nabil; Lucia Cyrilla; Iyep Komala (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The purpose of this study was to evaluate good dairy farming practices and good milking practices in dairy farms in Tajur Halang Village, to determine the perceptions of farmers, village administrators, and local governments towards the development of dairy farmer competencies for the development of tourist villages, and to formulate a livestock resource development model. This study was designed as a descriptive research. The instrument used in this study are a 4-point Likert scale questionnaire, and Good Dairy Farming Practices (GDFP), and Good Milking Practices (GMiP) evaluation form. Data collection was conducted through interviews with 45 dairy farmers, village administrators, and local governments, Focus Group Discussions (FGDs) on the solidarity of alumni of the Indonesian People's Animal Husbandry School (SASPRI), while the formulation of a model for improving dairy farmer competencies was carried out using the Participatory Rural Appraisal technique (PRA). The results showed that the GDFP and GMiP values ​​of dairy farms in Tajur Halang Village were in the "Good" category. Stakeholder perceptions showed a high level of suitability for efforts to develop dairy farmer competencies. The formulation of the livestock farmer competency development model yielded three main pillars: tourism village development, program development, and training and mentoring. Based on these findings, dairy farmers already possess strong competencies in livestock farming. However, these competencies are not sufficient for them to play an active role in tourism villages, as they still need to master social and tourism competencies.